Closed-loop recyclable silica-based nanocomposites with multifunctional properties and versatile processability - Hou, Yi; Zhu, Guangda; Catt, Samantha; Yin, Yuhan; Xu, Jian; Blasco, Eva; Zhao, Ning (Advanced science, 2023)
Most plastics originate from limited petroleum reserves and cannot be effectively recycled at the end of their life cycle, making them a significant threat to the environment and human health. Closed-loop chemical recycling, by depolymerizing plastics into monomers that can be repolymerized, offers a promising solution for recycling otherwise wasted plastics. However, most current chemically recyclable polymers may only be prepared at the gram scale, and their depolymerization typically requires harsh conditions and high energy consumption. Herein, it reports less petroleum-dependent closed-loop recyclable silica-based nanocomposites that can be prepared on a large scale and have a fully reversible polymerization/depolymerization capability at room temperature, based on catalysis of free aminopropyl groups with the assistance of diethylamine or ethylenediamine. The nanocomposites show glass-like hardness yet plastic-like light weight and toughness, exhibiting the highest specific mechanical strength superior even to common materials such as poly(methyl methacrylate), glass, and ZrO2 ceramic, as well as demonstrating multifunctionality such as anti-fouling, low thermal conductivity, and flame retardancy. Meanwhile, these nanocomposites can be easily processed by various plastic-like scalable manufacturing methods, such as compression molding and 3D printing. These nanocomposites are expected to provide an alternative to petroleum-based plastics and contribute to a closed-loop materials economy.